Corporate governance in the Nigerian banking industry: towards governmental engagement. (26th October 2012) - Adegbite, Emmanuel
The recent global economic crisis has led to reduced confidence in the self–regulation of banks and has facilitated a debate on how governments across the world intend to engage with the corporate governance of banks. In providing insights into this debate, this conceptual paper discusses the sectoral peculiarities of banks' corporate governance and in particular how these shape the philosophy and configuration of corporate governance regulation in banks. It presents a case study of the Nigerian banking sector in order to bring perspectives from sub–Saharan Africa which suffers from the dearth of literature. Taking into consideration the regulatory challenges in the Nigerian banking sector, it examines the regulatory role of government and enforcement of regulations, and argues that more governmental involvement is needed in the corporate governance of banks (as opposed to other companies). This paper adds to the very limited studies on the role of government in the corporate governance.